The decline in dental caries among Belgian children between 1983 and 1998 - Carvalho JC, Van Nieuwenhuysen JP, D’Hoore W (Blackwell Synergy, 2001)
to investigate cross-sectionally a probable dental caries decline in Belgian 12-yr-olds and to analyse some factors that may be associated with dental caries during the study period. Methods: In the region of Brussels, children in the 7th grade at the same schools were sampled in 1983 (n½533) and 1998 (n½ 496).